2022
DOI: 10.1021/acsami.2c12181
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Co-catalyst/Facet Junction for Enhanced Photoelectrochemical Water Splitting

Abstract: Rational construction of electric field via assembling appropriate co-catalysts on anisotropic facets is of great significance for improving the photogenerated charge separation efficiency. However, this strategy usually gives rise to Fermi-level pinning which is not contributive to the charge separation but deleterious to the photoelectrochemical performance through consuming the measurable photovoltage. Herein, we demonstrate that manganese dioxide electrodeposited on the (111) facet of titanium dioxide nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…83 Min et al demonstrated that the formed junction between MnO 2 and the (111) plane of TiO 2 could provide a stronger interface electric eld for boosting the catalytic activity owing to the betting energy levels. 84 Although the above strategies have achieved a favourable effect to some This journal is © The Royal Society of Chemistry 2023 extent, the barrier of charge transfer cannot be completely removed.…”
Section: Selective Interfacial Bondingmentioning
confidence: 99%
“…83 Min et al demonstrated that the formed junction between MnO 2 and the (111) plane of TiO 2 could provide a stronger interface electric eld for boosting the catalytic activity owing to the betting energy levels. 84 Although the above strategies have achieved a favourable effect to some This journal is © The Royal Society of Chemistry 2023 extent, the barrier of charge transfer cannot be completely removed.…”
Section: Selective Interfacial Bondingmentioning
confidence: 99%
“…oxides, hydroxides, and layered double hydroxides have exhibited signicant promise in improving the catalytic activity of TiO 2 nanostructures. 5,7,10,11,[15][16][17] The mixed transition metal oxidebased OECs incorporated with TiO 2 boost the electrical conductivity and enhance active sites for the OER, leading to improved PEC activity. 7,15 The OECs also reduce the water oxidation overpotential, efficiently drive the hole transfer from the photo harvester to the catalysts, and enhance the photoinduced charge carrier separation, resulting in enhanced surface OER of the TiO 2 photoanodes.…”
Section: Introductionmentioning
confidence: 99%
“…7,15 The OECs also reduce the water oxidation overpotential, efficiently drive the hole transfer from the photo harvester to the catalysts, and enhance the photoinduced charge carrier separation, resulting in enhanced surface OER of the TiO 2 photoanodes. 5,10,11,[15][16][17] Recently, single-atom catalysts (SACs) have emerged as successful catalysts to enhance the kinetics of the OER/hydrogen evolution reaction (HER) for water splitting by reducing the utilization of precious metal catalysts. [18][19][20][21] Both the noble metal and nonnoble metalbased SACs have been directly dispersed on the TiO 2 photo harvester to maximize the catalytic efficiency of the isolated metal atoms and to modify the electronic structure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches encompass heteroatom doping [7,8], morphology manipulation [9,10], quantum dot sensitization [11], and so forth. While these methods effectively broaden TiO 2 working spectrum and consequently enhance photocurrent, the efficiency of charge separation remains relatively constrained, necessitating further advancements in TiO 2 -based photoanodes [12].…”
Section: Introductionmentioning
confidence: 99%